Reconstructing the expansion and consolidation of immigration detention infrastructure in Greece (1993-2018) - Castiglione, Débora (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2022)
Since the early 1990s, Greek migration policies have been characterized by limited pathways to regularization and for relying heavily in immigration detention. Despite many studies about Greece’s legal framework, policies, and migration movements towards the country, immigration detention infrastructure received almost no attention in the literature. This study reconstructs the expansion of immigration detention in the country between 1993-2018. It uses a methodology based on an analysis of reports made by the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment (CPT), whose descriptions of facilities were systematized and georeferenced for a territorial and qualitative analysis. We find that the expansion of immigration detention infrastructure in the country occurred in three stages, corresponding to different spatial tactics of migration control. The results are discussed in light of the growing literature on immigration detention.